Ischemia reperfusion injury facilitates lung allograft acceptance through IL‐33‐mediated activation of donor‐derived IL‐5 producing group 2 innate lymphoid cells. Issue 8 (17th May 2022) - Guo, Yizhan; Mei, Zhongcheng; Li, Dongge; Banerjee, Anirban; Khalil, May A.; Burke, Allen; Ritter, Jon; Lau, Christine; Kreisel, Daniel; Gelman, Andrew E.; Jacobsen, Elizabeth; Luzina, Irina G.; et al.
Abstract : Pathways regulating lung alloimmune responses differ from most other solid organs and remain poorly explored. Based on our recent work identifying the unique role of eosinophils in downregulating lung alloimmunity, we sought to define pathways contributing to eosinophil migration and homeostasis. Using a murine lung transplant model, we have uncovered that immunosuppression increases eosinophil infiltration into the allograft in an IL‐5‐dependent manner. IL‐5 production depends on immunosuppression‐mediated preservation of donor‐derived group 2 innate lymphoid cells (ILC2). We further describe that ischemia reperfusion injury upregulates the expression of IL‐33, which functions as the dominant and nonredundant mediator of IL‐5 production by graft‐resident ILC2. Our work thus identifies unique cellular mechanisms that contribute to lung allograft acceptance. Notably, ischemia reperfusion injury, widely considered to be solely deleterious to allograft survival, can also downregulate alloimmune responses by initiating unique pathways that promote IL‐33/IL‐5/eosinophil‐mediated tolerance. Abstract : Activated by ischemia‐reperfusion injury, donor‐derived, group 2 innate lymphoid cells facilitate lung allograft acceptance by recruiting tolerogenic eosinophils in an IL‐33/IL‐5 dependent manner.